From eyeless to neurological diseases. (March 2017) - Graw, Jochen
Abstract: Age-related cataracts are frequently associated with degenerative changes in the ocular lens including the aggregation of proteins – mainly crystallins, but also other proteins including amyloids (Aβ) leading to the hypothesis that cataracts could be used as "biomarkers" for Alzheimer disease. Even if this hypothesis was rejected by David Beebe's last paper (Bei et al., Exp. Eye Res., 2015), it is a fascinating aspect to look for commonalities between eye diseases and neurological disorders. In this review, I discuss such commonalities between eye and brain mainly from a developmental point of view. The finding of the functional homology of the Drosophila eyeless gene with the mammalian Pax6 gene marks a first highlight in the developmental genetics of the eye – this result destroyed the "dogma" of the different evolutionary routes of eye development in flies and mammals. The second highlight was the finding that Pax6 is also involved in the development of the forebrain supporting the pleiotropic role of many genes. These findings opened a new avenue for research showing that a broad variety of transcription factors, but also structural proteins are involved both, in eye and brain development as well as into the maintenance of the functional integrity of the corresponding tissue(s). In this review recent findings are summarized demonstrating that genes whose mutations have been identified first to be causative for congenital or juvenile eye disorders are also involved in regenerative processes and neurogenesis ( Pax6 ), but also in neurodegenerative diseases like Parkinson (e.g. Pitx3 ) or in neurological disorders like Schizophrenia (e.g. Crybb1, Crybb2 ). Highlights: Mutations in genes important for eye development are involved in neuronal processes. Mutations in Pax6 affect neurogenesis. Mutations in Pitx3 are involved in Parkinson's disease. Mutations Cryb1 / Crybb2 contribute to schizophrenia-like behavior.